2021
DOI: 10.1186/s12958-021-00722-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect prophylactic internal iliac artery balloon occlusion in patients with placenta previa or placental accreta spectrum: a systematic review and meta‐analysis

Abstract: Background Placenta previa describes a placenta that extends partially or completely over the internal cervical oss. Placenta previa is one of the leading causes of widespread postpartum hemorrhage and maternal mortality worldwide. Another cause of bleeding in pregnant women is Placenta accreta spectrum. Therefore, the aim of the present systematic review and meta-analysis is to determine the effect of prophylactic balloon occlusion of the internal iliac arteries in patients with placenta previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…A planned hysterectomy was performed as the woman didn't want to preserve fertility. The use of iliac artery balloons (in earlier cases placed in the internal iliac arteries and later in the common iliac arteries, as the latter will additionally block the supply to the placenta from the external iliac arteries) [17][18][19][20][21] was associated with a reduction in blood loss, although not statistically significant. This may have been related to the fact that the cases who had iliac balloons placed were the most complex and were expected to be associated with high blood loss.…”
Section: Discussionmentioning
confidence: 92%
“…A planned hysterectomy was performed as the woman didn't want to preserve fertility. The use of iliac artery balloons (in earlier cases placed in the internal iliac arteries and later in the common iliac arteries, as the latter will additionally block the supply to the placenta from the external iliac arteries) [17][18][19][20][21] was associated with a reduction in blood loss, although not statistically significant. This may have been related to the fact that the cases who had iliac balloons placed were the most complex and were expected to be associated with high blood loss.…”
Section: Discussionmentioning
confidence: 92%
“…Yet, conclusions have been conflicting even when study results were pooled. 12,13 Therefore, the procedure has not been endorsed by international guidelines although the procedure is considered by many PAS-specialized centers To our knowledge, this is the first study that validates a riskstratification scoring system of clinical outcomes of PAS, which was generated using machine-learning algorithms. However, the study is limited by a lack of global standardization of outcome measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic internal iliac artery balloon occlusion has been numerously investigated in women with placenta previa and PAS. Yet, conclusions have been conflicting even when study results were pooled 12,13 . Therefore, the procedure has not been endorsed by international guidelines although the procedure is considered by many PAS‐specialized centers based on their internal data 11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…IIABO cannot control the collateral flow from the external iliac artery; thus, previous research reported that it could not reduce bleeding [24,25]. A recent systematic review and meta-analysis, evaluating 29 articles, suggested IIABO in patients with placenta previa contributes to reducing intraoperative blood loss and hysterectomy [26]. Some recommend CIABO because it occludes both internal and external iliac arteries, but it also carries the risk of distal embolism of the leg.…”
Section: Balloon Occlusion In Obstetrics: Prophylactic Use and Proxim...mentioning
confidence: 99%